2011
DOI: 10.1017/s0029665111003296
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional determinants of cognitive aging and dementia

Abstract: The objective of this review is to provide an overview of nutritional factors involved in cognitive aging and dementia with a focus on nutrients that are also important in neurocognitive development. Several dietary components were targeted, including antioxidant nutrients, dietary fats and B-vitamins. A critical review of the literature on each nutrient group is presented, beginning with laboratory and animal studies of the underlying biological mechanisms, followed by prospective epidemiological studies and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0
7

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 153 publications
(111 citation statements)
references
References 199 publications
(316 reference statements)
2
102
0
7
Order By: Relevance
“…In addition, it was also shown that CFs in cocoa induce vasodilation of the peripheral and cerebral vascular system (Sorond et al, 2008;Francis et al, 2006), increasing brain blood flow and perfusion mainly through an improvement in nitric oxide bioavailability in endothelial cells (Heiss et al, 2010). Thus, in humans, CF-containing foods can be effective in protection against the development of age-related cognitive dysfunction, possibly reversing or with a restorative effect on certain aspects of age-related cognitive decline (Field et al, 2011;Morris, 2012). It is also worth noting here that insulin has positive effects on LTM formation in Lymnaea (Murakami et al, 2013a,b;Hatakeyama et al, 2014;Ito et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was also shown that CFs in cocoa induce vasodilation of the peripheral and cerebral vascular system (Sorond et al, 2008;Francis et al, 2006), increasing brain blood flow and perfusion mainly through an improvement in nitric oxide bioavailability in endothelial cells (Heiss et al, 2010). Thus, in humans, CF-containing foods can be effective in protection against the development of age-related cognitive dysfunction, possibly reversing or with a restorative effect on certain aspects of age-related cognitive decline (Field et al, 2011;Morris, 2012). It is also worth noting here that insulin has positive effects on LTM formation in Lymnaea (Murakami et al, 2013a,b;Hatakeyama et al, 2014;Ito et al, 2015b).…”
Section: Discussionmentioning
confidence: 99%
“…The MIND Diet focuses on foods and nutrients that scientific research has shown to be associated with prevention of dementia (123)(124)(125). This diet emphasizes inclusion of green leafy vegetables, nuts, berries, beans, whole grains (at least 3 servings/day), oily fish, poultry, olive oil, and wine and recommends limiting inclusion of red meat, butter/stick margarine, cheese, pastries, and sweets, as well as fried or fast foods (126).…”
Section: Grain-based Foods As Part Of Healthy Dietary Patternsmentioning
confidence: 99%
“…w badaniach wykazano, że pewne składniki odżywcze (kwasy tłuszczo-we omega-3, nukleotyd urydyny, cholina) przez zwiększa-nie stężenia fosfolipidów w błonach komórkowych przyczyniają się do tworzenia nowych połączeń nerwowych [16,17]. Podobną rolę odgrywa prawidłowa podaż witaminy B 12 , e i kwasu foliowego [25,26]. jednym z mechanizmów wpływających na rozwój zmian otępiennych przy niedoborze witaminy B 12 jest jej sprzężenie z metabolizmem homocysteiny.…”
Section: Dyskusjaunclassified